BIMBINGAN TEKNIS PENINGKATAN PRODUKTIVITAS USAHA DAN PENDAPATAN PETANI MELALUI PENERAPAN MANAJEMEN AGRIBISNIS DI DESA ALEBO, KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Abdul Gafaruddin; La Ode Alwi; Irfan Ido; Wa Kuasa Baka (Jurnal Pengabdian NUSANTARA, 2023)
The ability of agricultural business human resources in rural areas in business management is still lacking because most of them have low education, only based on experience and training or counseling from related agencies. Most of the business capital comes from their own capital and partly is a capital strengthening fund from the government for the community through the Department of Agriculture. Production management is still simple and the marketing of agricultural business products is mainly marketed in the form of logs and is still on a local scale. Therefore, efforts to develop community businesses in rural areas are needed, one of which is through business management technical guidance. Business Management technical assistance is part of Partnership Technical Guidance Activities. To Improve the Quality of Human Resources in Southeast Sulawesi which was carried out by the Southeast Sulawesi Provincial Agriculture Service on 19 - 20 September 2022 which was attended by 20 participants. The results of the technical assistance showed that the majority (70%) of the training participants knew and were able to explain the importance of recording business transactions, while 10 people (50%) were able to record business transactions and 5 people (25%) had continued with the preparation of financial reports. (income statement and balance sheet). In addition, participants have also tried to utilize the information from the financial statements to make future business projections.